A new species of Spurostigma Eertmoed (Psocodea:’Psocoptera’: Spurostigmatidae) from Brazil - Da Silva Neto, Alberto Moreira; Aldrete, Alfonso N. García (Zootaxa, 2012)
A new species of Spurostigma, the first recorded in Brazil, is here described and illustrated. It differs from all the speciesin the genus, in which the male is known, in wing venation and in phallosome structure. It is the thirteenth known species of Spurostigma and the fourth species known from South America.